First report of Helicina chionea Pilsbry, 1949 from Brazil (Gastropoda, Helicinidae) and new records of Helicina spp. from Acre - Rodrigo Brincalepe Salvador; Marcos Silva de Lima; Wendel Castro Lima; Luiz Ricardo Lopes Simone; Edson Guilherme (Check List, 2020)
The present study stems from initial efforts in surveying the terrestrial gastropod fauna of Acre state, an undersampled Amazonian region in northwestern Brazil. Herein, we report the first record of the operculate snail Helicina chionea Pilsbry, 1949 in Brazil, alongside the first records of two other helicinids from Acre: H. juruana Ihering, 1905 and H. laterculus F.C. Baker, 1914. With the present new record, there is a total of 38 helicinid species reported from Brazil.